Potensi Aktivitas Antikanker Ekstrak Etanol Daun Peperomia pellucida L. Kunth Terhadap Lini Sel HSC-3 - Fitriani, Sabina; Sandra, Ferry (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: One of the most prevalent cancers worldwide is oral cancer, with approximately 90% of cases being squamous cell carcinoma. P. pellucida has potential as a chemopreventive agent due to its secondary metabolites, including flavonoids, which are known to have anticancer activity. Objective: The review aimed to explore potential directions for future research on treatment of oral cancer using of P. pellucida. Method: The references for this review were gathered from Google Scholar, PubMed, official reports, and global health organizations websites, using keywords like “Peperomia pellucida L. Kunth”, “apoptosis”, “oral cancer”, “anticancer”, and “HSC-3 cell line” from 2014 to 2024. This review considered references available in both English and Indonesian. Main finding: P. pellucida has been used in anticancer research due to its content of various phytochemical compounds, such as flavonoids. Previous studies have demonstrated the anticancer properties of P. pellucida against MCF-7, HT-29, and THP-1 cell lines. However, research specifically examining the anticancer potential of P. pellucida against oral cancer has not been reported. Conclusion: Several studies have reported that P. pellucida demonstrates potential as an anticancer agent. Further investigation is required to explore its capability in oral cancer therapy.